Preoperative serum placenta growth factor level as a new marker for stage II or III colorectal cancer patients - Özgür KEMİK and Ahu Sarbay Kemik and Aziz SÜMER and Sevim PURİSA and Barış TÜKENMEZ and Sefa TÜZÜN (Turkish Journal of Gastroenterology, 2019)
-